Eco-mechanisms within economic evolution: Schumpeterian approach - Agnieszka Lipieta; Andrzej Malawski (Journal of Economic Structures, 2021)
Supporting ecological innovations and economic activities which lead to environmental protection is one of the important challenges to decision-makers. The above is related to the problem of specification of mechanisms resulting in introducing ecological innovations to the economy. The original vision of the economic evolution determined by innovation was firstly presented by Joseph Schumpeter who identified essential innovative changes as well as indicated different mechanisms governing the economic evolution. The aim of the paper is to suggest a cohesive topological approach maintained in the stream of Schumpeter's thought, to study changes in the economy, which result in the elimination of at least one harmful commodity or technology from the market, by incorporating Hurwicz apparatus in a suitably modified competitive economy. Qualitative properties of mechanisms which can occur within the economic evolution are also analyzed.
Keywords: D41; D50; O31; 330; Eco-innovation; Eco-mechanism; Economic evolution; Ökologie; Innovation; Technischer Fortschritt; Evolutionsökonomik; Schumpeterismus; Wettbewerbstheorie